A preliminary report of Gymnopus sect. Impudicae (Omphalotaceae) from China - Li, Ji-Peng; Li, Yu; Li, Tai-Hui; Antonín, Vladimír; Hosen, Md Iqbal; Song, Bin; Xie, Meng-Le; Feng, Zhan (Phytotaxa, 2021)
A new species, Gymnopus alliifoetidissimus, is described from China. It represents the first new species of Gymnopus sect. Impudicae for this country. It is characterized by its small, white basidiomata with a strong alliaceous smell. Additionally, G. densilamellatus and G. similis, originally described from South Korea, are reported as new records to China. Detailed descriptions, colour photographs, illustrations of microcharacters and phylogenetic analyses based on nrDNA (ITS1-5.8S-ITS2-nrLSU) are presented. All known Chinese species were summarised in a preliminary report based on relevant literature and this study, and a key to the reported species of G. sect. Impudicae from China is provided.